SNP detection of TLR8 gene, association study with susceptibility/resistance to GCRV and regulation on mRNA expression in grass carp, Ctenopharyngodon idella. Issue 1 (March 2015) - Su, Juanjuan; Su, Jianguo; Shang, Xueying; Wan, Quanyuan; Chen, Xiaohui; Rao, Youliang
Abstract Toll-like receptor 8 (TLR8), a prototypical intracellular member of TLR family, is generally linked closely to antiviral innate immune through recognizing viral nucleic acid. In this study, 5′-flanking region of Ctenopharyngodon idella TLR8 (CiTLR8), 671 bp in length, was amplified and eight SNPs containing one SNP in the intron, three SNPs in the coding region (CDS) and four SNPs in the 3′-untranslated region (UTR) were identified and characterized. Of which 4062 A/T was significantly associated with the susceptibility/resistance to GCRV both in genotype and allele (P < 0.05), while 4168 C/T was extremely significantly associated with that (P < 0.01) according to the case (susceptibility)–control (resistance) analysis. Following the verification experiment, further analyses of mRNA expression, linkage disequilibrium (LD), haplotype and microRNA (miRNA) target site indicated that 4062 A/T and 4168 C/T in 3′-UTR might affect the miRNA regulation, while the exertion of antiviral effects of 4062 A/T might rely on its interaction with other SNPs. Additionally, the high-density of SNPs in 3′-UTR might reflect the specific biological functions of 3′-UTR. And also, the mutation of 747 A/G in intron changing the potential transcriptional factor-binding sites (TFBS) nearby might affect the expression of CiTLR8 transcriptionally or post-transcriptionally. Moreover, as predicted, the A/G transition of the only non-synonymous SNP (3846 A/G) in CDS causing threonine/alanine variation, could shorten the length of the α-helix and ultimately affect the integrity of the Toll-IL-1 receptor (TIR) domain. The functional mechanism of 3846 A/G might also involve a threonine phosphorylation signaling. This study may broaden the knowledge of TLR polymorphisms, lay the foundation for further functional research of CiTLR8 and provide potential markers as well as theoretical basis for resistance molecular breeding of grass carp against GCRV.